Cough-Induced Groin Pain: Misleading Symptom or Diagnostic Key for Differential Diagnosis. - Yıldırım, Seçil; Ayyıldız, Aylin; Temel, Mustafa Hüseyin; Bağcıer, Fatih; Coşkun, Evrim (Clinical Medicine Insights: Arthritis & Musculoskeletal Disorders, 2026)
Groin pain that worsens with coughing is most commonly attributed to intra-abdominal pressure changes associated with inguinal or femoral hernias. However, musculoskeletal (MSK) disorders can mimic hernia-related symptoms and are often overlooked, leading to misdiagnosis, unnecessary imaging, and delayed treatment. Recognition of these alternative causes is essential for accurate diagnosis and appropriate management. We report the case of a 42-year-old male office worker with chronic right-sided groin pain persisting for 6 months. The pain was localized without radiation, aggravated by palpation, but not influenced by coughing or the Valsalva maneuver. Imaging studies including MRI of the hip, lumbar spine, and pelvis were unremarkable. On physical examination, a hypersensitive trigger point was identified in the pectineus muscle, with a pain pressure threshold (PPT) of 1.8 kg/cm2 compared to 3.4 kg/cm2 on the unaffected side. A diagnosis of pectineus myofascial pain syndrome was made. Ultrasound-guided dry needling was applied in three sessions over 2 weeks, resulting in an improvement of PPT to 3.2 kg/cm2 and a reduction of the Visual Analog Scale (VAS) score from 7/10 to 2/10. This case emphasizes that not all groin pain provoked by coughing is hernia-related. Pectineus myofascial pain syndrome, although underrecognized, should be considered in the differential diagnosis. Early recognition of this condition can prevent unnecessary surgical referrals and facilitate timely effective treatment.